Novel gut bacteria species Paenibacillus ilasis with phosphorus degrading and soluble starch hydrolysis abilities isolated from fresh feces of rhinoceros - Xue Li; Shuyu Zuo; Ming Li; Qin Li; Lei Su (Scientific Reports)
Abstract The genus Paenibacillus, known for its diverse sources, is a valuable reservoir of antimicrobial compounds, enzymes and other valuable chemicals, with applications in medicine, agriculture, and bioremediation. Despite this, Paenibacillus strains, particularly those isolated from unique environments, remain underexplored, limiting our understanding of their potential, capabilities and taxonomic classifications. The gut microbiome of large herbivores, such as rhinoceroses, harbors underexplored microbial diversity with unique metabolic capabilities. In this study, a Gram-stain-negative, facultatively aerobic, motile, spore-forming, rod-shaped bacterial strain, NGMCC 1.200843T (= CGMCC 1.64763T = JCM 37214T), was isolated from fresh rhinoceros feces and characterized its taxonomic status and metabolic potential. Phylogenetic, phenotypic, and chemotaxonomic analyses confirmed the isolate as a novel species within the genus Paenibacillus, closely related to Paenibacillus lautus DSM 3035T (98.62% 16S rRNA gene similarity). The average nucleotide identity (ANI) and the digital DNA–DNA hybridization values were below the threshold for species delineation. The major cellular fatty acids were anteiso-C15:0, C16:0 and iso-C16:0 (> 10%) and the polar lipid profile contained diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), phosphatidylethanolamine (PE), two unidentified phospholipids (PL1–2) and one phosphatidyl choline (PC). The total DNA G + C content was 49.69 mol%. The isolate exhibited significant phosphate solubilization and starch hydrolysis activities in plate assays, suggesting a role in nutrient cycling within the rhinoceros gut. We propose the name Paenibacillus ilasis sp. nov. for this strain. These findings enhance our understanding of gut microbial diversity in herbivores and lay the foundation for future applications in agriculture or industry.